Destructive adsorption of methyl parathion over nanocrystalline MgO - Reddy, V. S.; RadheShyam, A.; Dwivedi, Reena; Gupta, R. K.; Chumbhale, Vilas R.; Prasad, R. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2005)
Destructive adsorption of methyl parathion (MP) has been investigated over few transition metal oxides and alkali earth metal oxides. Performance of alkaline earth oxides have been found to be better than transition metal oxides and best performance has been shown by aerogel method prepared nanocrystalline AP-MgO. The AP-MgO powder has been characterized by XRD, AFM and BET surface area measurements. Destructive adsorption of MP over AP-MgO has been compared with that of activated carbon. Both are found to adsorb methyl parathion effectively. An IR investigation of the surface of treated AP-MgO and activated carbon reveals that activated carbon adsorbs methyl parathion as such in the molecular form and AP-MgO adsorbs it destructively.

Vapour phase methylation of phenol over nanocrystalline ZnFe(2-x)A1(x)O(4) (x=0, 0.25, 0.5, 0.75 and 1.0) ferrospinel system - Reddy, Vanga S.; RadheShyam, A.; Dwivedi, Reena; Rai, A.; Anilkumar, Mettu; Chumbhale, Vilas R.; Aswar, A. S.; Prasad, R. (Indian Journal of Chemical Technology, 2006)
The alkylation ofphenol with methanol was carried out over ZnFe2-xAlxO4 (x = 0, 0.25, 0.5, 0.75 and 1.0) type spinel systems in a Fixed bed, down flow reactor. The influence of Surface acidity, cation distribution in the spinel lattice and various reaction parameters are discussed. A maximum yield of 70.9 and 22.9% with selectivity of 73.5 and 23.3% was obtained for 2,6-xylenol and o-cresol respectively, giving a total ortho selectivity of: 96.8% over ZnFeAlO4 at 350 degrees C, methanol to phenol molar ratio of 5 and WHSV of 0.6 h(-1). Catalyst characterization was made by XRD, Mossbauer spectroscopy, ammonia desorption and BET surface area measurements. Mossbauer spectroscopy reveals isomorphic substitution or Fe 3 by smaller A 13, into the octahedral sites leading to lattice distortion, Unsymmetrical charge distribution and charge transfer from iron to oxygen making it more basic and proton attracting. This helps vertical adsorption ofphenol and formation of 2.6-xylenol. It has been concluded that catalyst acidity plays major role in the reaction as compared to surface area.
Keywords: consecutive methylation; ferrospinels; vertical and horizontal adsorption